2009
DOI: 10.1510/icvts.2009.209890
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective analysis of terlipressin in bolus for the management of refractory vasoplegic hypotension after cardiac surgery

Abstract: Cardiac surgery performed with cardiopulmonary bypass (CPB) may be complicated by hypotension due to low systemic vascular resistance (SVR). Often in those cases, hypotension is resistant to pressor catecholamines. We report six cases of norepinephrine-resistant postcardiotomy hypotension, treated by terlipressin (TP), a potent vasopressor agent. Between May 2007 and May 2008, we treated six patients with TP administration (1 mg bolus) for post CPB refractory vasodilatory hypotension. Analyzed parameters were:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…192 Vasopressors (epinephrine, norepinephrine, vasopressin, terlipressin, phenylephrine, metaraminol, methylene blue, hydroxocobalamin and combinations) are required to treat vasoplegic syndrome during CPB. 194,195 In an RCT enrolling patients under angiotensin-converting enzyme inhibitors, methylene blue was effective for the prevention/treatment of vasoplegic syndrome (compared to saline), resulting in lower lactate levels during and after CPB. 196 In a similar patient population, vasopressin was effective in preventing/treating vasoplegic syndrome compared to saline.…”
Section: Description Of the Evidencementioning
confidence: 99%
“…192 Vasopressors (epinephrine, norepinephrine, vasopressin, terlipressin, phenylephrine, metaraminol, methylene blue, hydroxocobalamin and combinations) are required to treat vasoplegic syndrome during CPB. 194,195 In an RCT enrolling patients under angiotensin-converting enzyme inhibitors, methylene blue was effective for the prevention/treatment of vasoplegic syndrome (compared to saline), resulting in lower lactate levels during and after CPB. 196 In a similar patient population, vasopressin was effective in preventing/treating vasoplegic syndrome compared to saline.…”
Section: Description Of the Evidencementioning
confidence: 99%
“…Furthermore, Boccara et al found that patients undergoing carotid endarterectomy who had hypotension refractory to ephedrine had less hypotensive episodes when treated with terlipressin as opposed to norepinephrine. Few other studies have demonstrated the efficacy of AVP analogs in catecholamine refractory VS . However, use of RASi preoperatively in these studies was not reported.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, MB is recommended only as a rescue therapy for treating post-cardiac surgery VPS. 29 High doses of hydroxocobalamin (5 gm iv bolus over 15 min, and maximum of 10 g) have been used successfully as a rescue therapy in a case report of refractory VPS during cardiac surgery on CPB, that was unresponsive to high doses of epinephrine, NE, vasopressin, and MB. 12 Therefore, hydroxocobalamin has been recommended only as a rescue therapy in VPS unresponsive to other vasopressors.…”
Section: Non-vasopressor Therapy: Ascorbic Acid Thiamine Corticostero...mentioning
confidence: 99%